Evaluation of angiotensin converting enzyme 2 - Kakavandi, Ehsan; Sadeghi, Kaveh; Shayestehpour, Mohammad; Mirhendi, Hossein; Rahimi Foroushani, Abbas; Mokhtari-Azad, Talat; Shafiei Jandaghi, Nazanin Zahra; Yavarian, Jila (BMC infectious diseases, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly contagious virus that uses angiotensin converting enzyme 2 (ACE2), a pivotal member of the renin-angiotensin system (RAS), as its cell-entry receptor. Another member of the RAS, angiotensin II (Ang II), is the major biologically active component in this system. There is growing evidence suggesting that serum miRNAs could serve as prognostic biomarkers for SARS-CoV-2 infection and regulate ACE2 expression. Therefore, the aim of this study is to evaluate the changes in the serum levels of sACE2 and Ang II, as well as the expression level of miR-141-3p and miR-421 in SARS-CoV-2 positive and negative subjects. In the present study, the serum levels of sACE2 and Ang II were measured in 94 SARS-CoV-2 positive patients and 94 SARS-CoV-2 negative subjects with some symptoms similar to those of SARS-CoV-2 positive patients using the ELISA method. In addition, the expression level of miR-141-3p and miR-421 as ACE2 regulators and biomarkers was evaluated using quantitative real-time PCR (qRT-PCR) method. The mean serum sACE2 concentration in the SARS-CoV-2-positive group was 3.268 [+ or -] 0.410 ng/ml, whereas in the SARS-CoV-2 negative group, it was 3.564 [+ or -] 0.437 ng/ml. Additionally, the mean serum Ang II level in the SARS-CoV-2 positive and negative groups were 60.67 [+ or -] 6.192 ng/L and 67.97 [+ or -] 6.837 ng/L, respectively. However, there was no significant difference in the serum levels of sACE2 (P value: 0.516) and Ang II (P value: 0.134) between the SARS-CoV-2 positive and negative groups. Meanwhile, our findings indicated that the expression levels of miR-141-3p and miR-421 in SARS-CoV-2 positive group were significantly lower and higher than SARS-CoV-2 negative group, respectively (P value < 0.001). Taken together, the results of this study showed that the serum levels of sACE2 and Ang II in SARS-CoV-2 positive and negative subjects were not significantly different, but the expression levels of miR-141-3p and miR-421 were altered in SARS-CoV-2 positive patients which need more investigation to be used as biomarkers for COVID-19 diagnosis.